Effects of acceptance and commitment therapy on the perception of the impact on the family in the context of childhood cancer: A case study - Trejo Ramos, Diana Gabriela; García Flores, Raquel; Sotelo Quiñonez, Teresa Iveth; Acosta Quiroz, Christian Oswaldo; Castrejón Salgado, Ricardo (Psicooncología, 2025)
Introduction. The impact that mothers face when a disease such as childhood cancer occurs has been demonstrated. The application of evidence- based interventions can contribute to the mental health of people in charge of caring for infants with cancer. Aim. The present work evaluates the effect of acceptance and commitment therapy on the perceived impact of the illness in a mother through a brief intervention program. Method. A single case study of type A-B-A was carried out, the participant is a mother of a child with Leukemia; The instruments included the Family Impact Module Questtionaire (PedsqL), the Acceptance and Action Questionnaire (AAQ-II) and the Satisfaction with the Treatment Received Scale (CRES-4). Results. Through visual analysis and through Tau-U, it was evidence that the Acceptance and Commitment Therapy protocol has significant effects on the reduction of experiental avoidance and the perception of family impact. Through the analysis with the Tau-U test, a significant Omnibus average was identified in the perception of family impact (0.0495, p .05), as well as in the factors: social functioning (0.0175, p< .05), cognitive functioning (0.0336, p< .05) and daily activities (0.0087, p< .05). Conclusions. ACT has a stasistically relevant effect on the perception of family impact and on the factors that make it up, so it is considered to continue with lines of research that promote its use in health and vulnerabily context.